2021
DOI: 10.1186/s12954-021-00509-0
|View full text |Cite
|
Sign up to set email alerts
|

Gaps in evidence for the use of medically authorized cannabis: Ontario and Alberta, Canada

Abstract: Background With legal access to medical cannabis in Canada since 2001, there is a need to fully characterize its use at both the individual and population levels. We draw on data from Canada’s largest cohort study of medical cannabis to identify the primary reasons for medical cannabis authorization in Canada from 2014 to 2019 in two major provinces: Alberta (AB) and Ontario (ON), and review the extent that evidence supports each indication. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…21 Most studies on cannabis use patterns among cancer patients are limited to a single site lacking large-scale studies. 25 This result corroborates with the work of Noori A et al, 26 which showed that Colombian psychiatrists have a favorable attitude toward prescribing medical cannabis; however, there is a serious lack of legal knowledge. [23][24][25][26] An interesting finding in the study by Kaufmann et al,8 was that most physicians agreed with the use of (CM) to combat chronic cancer-related pain receiving the highest approval with 87.6%.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…21 Most studies on cannabis use patterns among cancer patients are limited to a single site lacking large-scale studies. 25 This result corroborates with the work of Noori A et al, 26 which showed that Colombian psychiatrists have a favorable attitude toward prescribing medical cannabis; however, there is a serious lack of legal knowledge. [23][24][25][26] An interesting finding in the study by Kaufmann et al,8 was that most physicians agreed with the use of (CM) to combat chronic cancer-related pain receiving the highest approval with 87.6%.…”
Section: Discussionsupporting
confidence: 86%
“…[23][24][25][26] An interesting finding in the study by Kaufmann et al,8 was that most physicians agreed with the use of (CM) to combat chronic cancer-related pain receiving the highest approval with 87.6%. [24][25] ,…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Legalization of cannabis in many jurisdictions around the world has the potential to lead to greater availability and accessibility of cannabis products for all age groups [10]. As North American baby boomers born in the 1950s and 1960s age, attitudes toward cannabis use in the older adult cohort have changed, leading to higher rates of use in this demographic [2,116,168,169].…”
Section: Discussionmentioning
confidence: 99%
“…Older adults generally suffer from more chronic health conditions than younger adults (e.g., chronic pain, insomnia) [6,7] and, thus, may be attracted to cannabis for medical purposes [3,8] by marketing efforts that exaggerate the medical and "wellness" benefits of cannabis, while minimizing its harms [9], and by word-of-mouth anecdotal "evidence." Legalization, increased access, and non-evidence-based marketing may plausibly increase the proportion of older adults who consume cannabis for both medical and non-medical purposes [10]. Past work has suggested medical cannabinoids may offer certain benefits from consumption when conventional treatment does not help for conditions that include neuropathic pain, chemotherapy induced nausea and vomiting, spasticity (from multiple sclerosis and spinal cord injury), palliative and end-of-life pain [11].…”
Section: Introductionmentioning
confidence: 99%